PEMBERDAYAAN MASYARAKAT BERBASIS EKONOMI KREATIF DI KAWASAN WISATA TARUSAN KAMANG SUMATERA BARAT - Ifni Amanah Fitri (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2019)
The objectives of the article are to identify the background of the emergence of empowerment in the community in the tourist area of Tarusan Kamang and the forms of creative economy-based community empowerment in the tourist area of Tarusan Kamang. The method used is a qualitative method with a type of descriptive research that describes the circumstances that occur in the field about creative economy-based community empowerment in the Kamang Tarusan tourism area, which is experienced by research subjects. The source of data from this study is the community that carries out community-based creative economic empowerment and the government of Jorong Halalang and the data obtained from the documents. While data collection techniques are observation, interviews, and documentation studies. The results of this study reveal that creative economy-based community empowerment in the Kamang Tarusan tourism area are: (1) The background of the emergence of community empowerment in the Kamang Tarusan tourism area is caused by three factors: low economic conditions, the presence of tourist areas, and the participation of migrants. (2) Forms of community empowerment based on the creative economy, namely: providing food and resting places, providing crossing equipment, displaying performing arts, and utilizing lake products.